Ammo for the info warrior - Media Education Foundation; Media Education Foundation; Guerilla News Network ([Northampton, Mass.] : Media Education Foundation, 2002)
A collection of nine news videos created by Guerilla News Network (GNN), an independent news organization devoted to exposing young people to global news and information. The videos cover a range of stories, from the diamond trade in Sierra Leone to the public relations industry practices to spoken word poetry about the business of hip-hop
Countdown: Ralph Nader remix on politics, big business, the media system and democracy - Crack the CIA - The war conspiracy - When the smoke clearz - the most dangerous game - The diamond life - 9-11 redux - John Stauber: stealing the spin from the PR industry - Robert Sterling: guerilla warfare in the information age
Title from container
Keywords: Mass media and youth; Mass media and young adults; Mass media and education; Documentary films